2021
DOI: 10.3390/met11071068
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rate and Deformation of External Hexagon Implants with One-Piece Zirconia Crowns

Abstract: This study aimed to evaluate the survival rates of several external hexagon implants directly connected to zirconia crowns after thermomechanical fatigue. The deformation of the hexagons and the integrity of zirconia crowns were also evaluated. A monolithic zirconia crown (Y-TZP) and four different external hexagon dental implants (n = 10, N = 40) were mounted together and embedded in polyurethane. The specimens were subjected to thermomechanical cycling for 2.5 × 106 cycles, at 3.0 Hz frequency, at 200 N load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…With highly advantageous properties, zirconia ceramics are increasingly being used in fabricating infrastructures as well as monolithic restorations 2 . Zirconia is susceptible to phase transformation as it is a polymorphic material and has three main phases (monoclinic, tetragonal and cubic) 3–5 . The interest and ability to use zirconia in monolithic restorations 6 has recently been increasing, especially due to the development of new generations of this material which have a higher translucency level that benefits its esthetics, 2 as well as the increased knowledge in working the material microstructure to obtain such property.…”
Section: Introductionmentioning
confidence: 99%
“…With highly advantageous properties, zirconia ceramics are increasingly being used in fabricating infrastructures as well as monolithic restorations 2 . Zirconia is susceptible to phase transformation as it is a polymorphic material and has three main phases (monoclinic, tetragonal and cubic) 3–5 . The interest and ability to use zirconia in monolithic restorations 6 has recently been increasing, especially due to the development of new generations of this material which have a higher translucency level that benefits its esthetics, 2 as well as the increased knowledge in working the material microstructure to obtain such property.…”
Section: Introductionmentioning
confidence: 99%
“…The strength and toughness of zirconia are attributable to mechanisms such as crack deflection, contact shielding, zone shielding, and crack bridging [ 38 ]. Zirconia abutments are available for the various types of implants, such as external and internal hexagon implants [ 39 ]. Although a review indicated that both externally and internally connected ceramic abutments are associated with higher fracture rates than are externally and internally connected metal abutments [ 2 ], no statistically or clinically significant differences between survival rates and the incidence of complications of zirconia and titanium abutments have been noted [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several design parameters that can modify the implants mechanical response have already demonstrated their role in the bone tissue mechanical response during chewing loading. For that reason, a possible variation in the stress magnitude between different implant manufacturers would be noticed due to the differences in threads design [42], conicity [43], length [44], diameter [45], abutment misfit [46], prosthetic connection [47], titanium alloys [40], torque quantity [48], abutment material [49] and antagonist structure [50]. However, despite the effect of all these factors have been already investigated in previous reports, the present results can be useful especially when considering the stress distribution modification by the implant neck design, that should occurs proportionally between the different implant systems.…”
Section: Discussionmentioning
confidence: 99%